2022
DOI: 10.1002/cncr.33880
|View full text |Cite
|
Sign up to set email alerts
|

Comparing clinical and nonclinical cancer patient navigators: A national study in the United States

Abstract: BACKGROUND:A nationwide survey was conducted to examine differences between clinical and nonclinical oncology navigators in their service provision, engagement in the cancer care continuum, personal characteristics, and program characteristics. METHODS: Using convenience sampling, 527 oncology navigators participated and completed an online survey. Descriptive statistics, χ 2 statistics, and t tests were used to compare nonclinical (eg, community health worker) and clinical (eg, nurse navigators) navigators on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
(78 reference statements)
0
7
0
Order By: Relevance
“…It is vital that the public has confidence in accessing a workforce that has a level of consistency in their service provision and outcomes. Wells and colleagues advocated for a consensus approach to determine core competencies of patient navigators 147 in which such competencies would be able to inform subsequent training curriculum and approaches.…”
Section: Discussionmentioning
confidence: 99%
“…It is vital that the public has confidence in accessing a workforce that has a level of consistency in their service provision and outcomes. Wells and colleagues advocated for a consensus approach to determine core competencies of patient navigators 147 in which such competencies would be able to inform subsequent training curriculum and approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we did not survey respondents on their navigation activities before the COVID‐19 pandemic. The 2019 NNRT national survey reported extensively on cancer navigation activities, drawing from a list of 38 navigation tasks, as reported elsewhere 35 . The current survey was administered using the same recruitment channels and likely surveyed many of the same cancer navigators.…”
Section: Discussionmentioning
confidence: 99%
“…Though national basic training programs exist (e.g., Harold P. Freeman Patient Navigation Institute; Colorado Patient Navigator Training), access to these centralized in-person trainings may be difficult for some navigators due to time and/or cost. Further, while research has demonstrated core tasks that many patient navigators perform, there is less agreement in the field on the core competencies of navigators [ 10 , 13 , 30 ]. Additional specialty training is likely required to acknowledge the variation and wide scope of needs to be addressed by different navigation programs in oncology or other settings [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are a growing number of nationwide studies describing common activities of oncology and other PN [ 10 – 13 ], but there is no consensus yet in the field regarding expectations for the PN role. Thus, it is not surprising that oncology navigator training practices vary widely, and are not well documented [ 6 ], and may depend on the professional certification of navigators [ 14 ].…”
Section: Introductionmentioning
confidence: 99%